Carbonic anhydrase inhibition with a series of novel benzenesulfonamide-triazole conjugates - Marwa G. El-Gazzar; Nessma H. Nafie; Alessio Nocentini; Mostafa M. Ghorab; Helmi I. Heiba; Claudiu T. Supuran (Taylor & Francis Group, 2018)
We report the synthesis and characterisation of a novel series of triazole benzenesulfonamide derivatives, which incorporate the general pharmacophore associated with carbonic anhydrase (CA, EC 4.2.1.1) inhibitors. The synthesised compounds were tested in vitro against four human carbonic anhydrase (hCA, EC 4.2.1.1) isozymes, hCA I, hCA II, hCA IV and hCA IX. The obtained results showed that the tumour-associated hCA IX was the most sensitive to inhibition with the synthesised derivatives, with the triazolo-pyridine benzenesulfonamides 14, 16 and 17 being the most effective inhibitors. Some selected compounds were chosen for a single dose anti-proliferative activity testing against a panel of 57 human tumour cell lines and show some anti-proliferative activity ex vivo.